Optimization of Domestic Wastewater Treatment with Biological Aerated Filter (BAF) Method Based on Bioball - Sa'diyah, Khalimatus; Iswara, Mochammad Agung Indra; Dewi, Listiyana Candra; Putri, Febby Anisa (Jurnal Teknik Kimia dan Lingkungan, 2024)
Domestic wastewater treatment using Biological Aerated Filter (BAF) method based on bioball is a technological innovation that combines biological and physical processes to improve effluent quality. This study studied the use of a Biological Aerated Filter (BAF) modified with bioball media and variations in residence time to improve waste treatment efficiency and ensure effluent quality by established standards. The study consisted of four stages: preparation, seeding and acclimatization, use of Biological Aerated Filter (BAF), and analysis of the results. The prepared waste samples are domestic liquid waste from shopping centers that have known sample parameters as influential. Seeding and acclimatization are carried out in BAF reactors. Waste was treated through BAF with variable residence time, then analyzed by testing procedures based on \SNI 6989.72: 2009. The results showed that the bioball media in the BAF reactor were more effective than without media, showing a decrease in TDS (92% in 6 hours), TSS (86%), and an increase in COD and BOD efficiency. Effluent pH results are constant at 6-7 as per environmental standards. Obtaining higher process efficiency required a combination of wastewater treatment methods.